Changing Trends in Liver Cirrhosis Etiology and Severity in Korea: the Increasing Impact of Alcohol - Yoon, Jae Hyun (J Korean Med Sci, 2021)
BACKGROUND: Chronic hepatitis B is the most common cause of liver cirrhosis in South Korea. However, alcoholic liver disease has shown an increasing trend. Although the clinical implications surrounding liver cirrhosis have been changing over the years, few studies have recently examined cirrhosis epidemiology. Therefore, we aimed to investigate changes in liver cirrhosis etiology and severity in Korea. METHODS: We retrospectively reviewed 16,888 records of cirrhotic patients from six tertiary hospitals in Korea from 2008 to 2017. Continuous and non-continuous variables were processed via linear and Poisson regression, expressed as beta (B) coefficients and as exponentiated values of coefficients (Exp[B]), respectively. RESULTS: Chronic hepatitis B showed a decreasing trend (Exp[B] = 0.975, P < 0.001), whereas alcohol showed an increasing trend (Exp[B] = 1.013, P = 0.003), occupying the most common etiology in 2017. The Child-Turcotte-Pugh (CTP) score and decompensated liver cirrhosis prevalence did not change over the 10-year period. The incidence of variceal bleeding, severe ascites, hepatic encephalopathy, and spontaneous bacterial peritonitis significantly decreased from 12.3% to 7.7%, 7.8% to 4.1%, 1.0% to 0.5%, and 1.9% to 1.1%, respectively (P < 0.05 for all). In the subgroup analysis, the chronic hepatitis B group showed improving CTP scores (B = −0.025, P < 0.001) and decreasing decompensated liver cirrhosis rates (Exp[B] = 0.977, P = 0.016), whereas the alcohol group demonstrated increasing CTP class C (Exp[B] = 1.031, P = 0.005) and model for end-stage liver disease scores (B = 0.081, P = 0.005) over 10 years. CONCLUSION: The chronic hepatitis B group exhibited improved results, whereas the alcohol group still presented poor liver functions and outcomes. Future national policies and systematic approaches addressing the incidence, prevention, and treatment of alcoholic liver cirrhosis are indispensable.